Exclusive Breastfeeding, Nutritional Status, and Diarrhea Incidence among Toddlers: Menyusui Eksklusif, Status Gizi, dan Insidensi Diare pada Balita - Jannah, Raudhatul Rayhannatil; Purwanti, Yanik; Rosyidah, Rafhani; Widowaty, Hesty (Universitas Muhammadiyah Sidoarjo, 2025)
Background : In Sidoarjo Regency, cases increased annually, with 65,813 cases recorded in 2021. Exclusive breastfeeding and adequate nutrition are crucial protective factors.Knowledge Gap: Previous studies identified various risk factors, yet limited evidence exists on their combined association in local community settings.Aim: This study examined the relationship between exclusive breastfeeding history and nutritional status with diarrhea incidence among toddlers in the Candi Sidoarjo Health Center area.Methods: A cross-sectional study was conducted on 45 mothers with toddlers aged 6–59 months using random sampling. Data were collected via questionnaires and anthropometric measurements, analyzed with chi-square tests.Results: Among toddlers, 60% received exclusive breastfeeding and 68.9% had normal nutritional status. Diarrhea incidence in the past three months was 55.6%. Chi-square analysis showed significant associations between exclusive breastfeeding (p=0.014) and nutritional status (p=0.037) with diarrhea occurrence.Novelty: The findings highlight how breastfeeding practices and nutritional adequacy collectively reduce diarrhea risk in community-level settings.Implications: Strengthening maternal awareness and nutrition interventions may lower diarrhea incidence and improve child health outcomes in similar populations. Highlights: Exclusive breastfeeding reduces diarrhea in toddlers Nutritional status significantly linked to diarrhea incidence Community-based evidence from Sidoarjo Keywords: Exclusive Breastfeeding, Nutritional Status, Diarrhea, Toddlers, Sidoarjo